Induction of CD4+CD25+ Regulatory T Cells from In Vitro Grown Human Mononuclear Cells by Sparteine Sulfate and Harpagoside - Nour Z. Atwany; Seyedeh-Khadijeh Hashemi; Manju Nidagodu Jayakumar; Mitzi Nagarkatti; Prakash Nagarkatti; Mona Rushdi Hassuneh (Biology, 2020)
Regulatory T cells (Tregs) are key players in the regulation of inflammatory responses. In this study, two natural molecules, namely, sparteine sulfate (SS) and harpagoside (Harp), were investigated for their ability to induce Tregs in human peripheral blood mononuclear cells (PBMCs). PBMCs were isolated from healthy volunteers and grown in the presence or absence of ConA, with TGF-beta, SS or Harp. Expression of the mRNA of FoxP3, TGF-beta, IL-10 and GAPDH was assessed via q-PCR. The expression of Treg markers including CD4, CD25, CD127 and FoxP3 was measured via flow cytometry. The secretion of IL-10 and TGF-beta by cultured cells was assessed by ELISA. Furthermore, the suppressive role of SS and Harp on PBMCs in vitro was tested via allogeneic mixed lymphocyte reaction (MLR). Data obtained show that both compounds increased the expression of FoxP3, TGF-beta and IL-10 mRNA in resting PBMCs but to a lesser extent in activated cells. Moreover, they significantly increased the percent of CD4+CD25+FoxP3+CD127− Tregs in activated and naïve PBMCs. Functionally, both compounds caused a significant reduction in the stimulation index in allogeneic MLR. Together, our data demonstrate for the first time that SS and Harp can induce human Tregs in vitro and therefore have great potential as anti-inflammatory agents.